2018
DOI: 10.1136/bmjopen-2017-021382
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Shared Care Program (DSCP) and risk of infection mortality: a nationwide cohort study using administrative claims data in Taiwan

Abstract: ObjectiveThe Diabetes Shared Care Program (DSCP) is an integrated care model in Taiwan that has been proven to improve the care quality of patients with diabetes. We aimed to evaluate the efficacy of DSCP in decreasing the hospital mortality of infectious diseases.MethodsFrom 1 662 929 patients with type 2 diabetes newly diagnosed between 1999 and 2013, we retrieved a total of 919 patients who participated in the DSCP with the first hospitalisation for an infectious disease as the study cohort and 9190 propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Major mortality causes other than infections included diseases of the circulatory system, respiratory system, endocrine, nutritional, and metabolic diseases [5]. Less literature discussed infection death among T2DM patients [18,32]. In our study, the risk of infection-related death and all-cause mortality were both significantly lower in the P4P group than in the non-P4P group, which is consistent with previous investigations [16,18,32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Major mortality causes other than infections included diseases of the circulatory system, respiratory system, endocrine, nutritional, and metabolic diseases [5]. Less literature discussed infection death among T2DM patients [18,32]. In our study, the risk of infection-related death and all-cause mortality were both significantly lower in the P4P group than in the non-P4P group, which is consistent with previous investigations [16,18,32].…”
Section: Discussionsupporting
confidence: 91%
“…Less literature discussed infection death among T2DM patients [ 18 , 32 ]. In our study, the risk of infection-related death and all-cause mortality were both significantly lower in the P4P group than in the non-P4P group, which is consistent with previous investigations [ 16 , 18 , 32 ]. The P4P program was suggested to result in more frequent measures of HbA1C and set appropriate target of glycemic control [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Chen et al demonstrated that participation in the DSCP programe was associated particularly with a lower risk of hospital mortality for infectious diseases than non-DSCP participants (2.18% vs 4.82%; p < 0.001). 36 Among the DSCP participants in our study, those with low individual SES had the highest risk of mortality, regardless of whether they lived in an advantaged or a disadvantaged neighborhood. Patients with low individual SES tended to live in rural and suburban areas or live in northern, central, and southern areas of Taiwan.…”
Section: Discussionmentioning
confidence: 63%
“…The examination of continued care and annual follow-ups will focus more on evaluation sections and based upon the baseline assessment (the details of items are provided in Additional file 1: Table S1) [7]. Hickman defined shared care as “the joint participation of hospital consultants and general practitioners in the planned delivery of care for patients with a chronic condition, informed by an enhanced information exchange over and above routine discharge and referral notes.” [8] Shared care also emphasizes multidisciplinary teamwork in diabetes management, including treating physicians, diabetes specialists, nurses, and dietitians [9]. Following the implementation of the DSCP, the standardized mortality rate in the diabetes population decreased from 39.8 in 2001 to 26.9 in 2011 [1].…”
Section: Introductionmentioning
confidence: 99%